Investigation on Open Badge and market - Katia Presutti; Lara Bovero; Cinzia Zedda; Cristina Fracchia; Manuela Caramagna; Gabriele Baratto; Cristina Giraudo; Federica Bassano (European Journal of Social Impact and Circular Economy, 2025)
This document investigates the transformative role of Open Badges and Blockchain technology in the educational sector, focusing on the University of Turin's (UniTo) "Premialità 2023" project. It discusses the development of a digital credential ecosystem using the Bestr platform, which employs Blockchain to ensure the transparency, security, and portability of academic credentials. The study highlights how digital credentials, particularly Open Badges, streamline the validation of skills and competencies and significantly contribute to social mobility and inclusivity. By providing a verifiable and accessible means of recognizing formal and informal learning, these technologies empower individuals from diverse backgrounds, enhancing their employability and participation in the workforce. Furthermore, the case study of UniTo showcases the potential of digital badges to bridge the gap between academic achievements and market needs, promoting a culture of continuous learning and adapting education to modern societal demands.